Southern Ocean CO2 sink: The contribution of the sea ice. Issue 9 (22nd September 2014) - Delille, Bruno; Vancoppenolle, Martin; Geilfus, Nicolas‐Xavier; Tilbrook, Bronte; Lannuzel, Delphine; Schoemann, Véronique; Becquevort, Sylvie; Carnat, Gauthier; Delille, Daniel; Lancelot, Christiane; Chou, Lei; Dieckmann, Gerhard S.; et al.
Abstract We report first direct measurements of the partial pressure of CO2 (pCO2) within Antarctic pack sea ice brines and related CO2 fluxes across the air‐ice interface. From late winter to summer, brines encased in the ice change from a CO2 large oversaturation, relative to the atmosphere, to a marked undersaturation while the underlying oceanic waters remains slightly oversaturated. The decrease from winter to summer of pCO2 in the brines is driven by dilution with melting ice, dissolution of carbonate crystals, and net primary production. As the ice warms, its permeability increases, allowing CO2 transfer at the air‐sea ice interface. The sea ice changes from a transient source to a sink for atmospheric CO2. We upscale these observations to the whole Antarctic sea ice cover using the NEMO‐LIM3 large‐scale sea ice‐ocean and provide first estimates of spring and summer CO2 uptake from the atmosphere by Antarctic sea ice. Over the spring‐summer period, the Antarctic sea ice cover is a net sink of atmospheric CO2 of 0.029 Pg C, about 58% of the estimated annual uptake from the Southern Ocean. Sea ice then contributes significantly to the sink of CO2 of the Southern Ocean.